Barriers and facilitators to the implementation of a novel web-based sleep apnea management platform. Issue 4 (20th November 2020) - Chang, Yoon Hee A; Folmer, Robert L; Shasha, Becky; Shea, Judy A; Sarmiento, Kathleen; Stepnowsky, Carl J; Lim, Diane; Pack, Allan; Kuna, Samuel T
Abstract: Study Objective: Obstructive sleep apnea (OSA) is a highly prevalent yet underdiagnosed disorder affecting US military Veterans. The Remote Veterans Apnea Management Platform (REVAMP) is a web-based OSA management program created to improve access to care. REVAMP was launched within the Veterans Health Administration (VHA) in July 2017, with variable patient recruitment rates (from 0 to 573 patients per site) at the first 10 Veterans Affairs (VA) medical centers (Wave-1 sites). This study aimed to examine the contextual circumstances surrounding the implementation of REVAMP from the provider perspective to inform strategies to increase its uptake at future rollout sites. Methods: A purposive sample of REVAMP site leaders from the Wave-1 sites was recruited with additional staff members being solicited as well. Semi-structured interviews were conducted. Two independent coders reviewed individual transcripts using content analysis to identify emerging themes. Results: Fifteen individuals from Wave-1 sites were interviewed. Implementation of REVAMP was facilitated by the presence of leadership support, staff, and time dedicated to REVAMP, and perceived usefulness of REVAMP by staff as well as positive feedback from the Veterans using REVAMP. The difficulty of supporting Veteran creation of login credentials to the program and integrating REVAMP into the existing workflow were major barriers to its implementation. Conclusion: Improving leadership engagement, simplifying the enrollment process, and enhancing the medical staff experience through shared best practice alerts were identified as actions needed to improve the penetration of REVAMP at future rollout sites.